Efficacy and Safety Evaluation of Mometasone Furoate in Treating Ocular Inflammation - Nayara Almeida Lage; Mayara Rodrigues Brandão de Paiva; Daniel Vitor Vasconcelos-Santos; Renes Resende Machado; Sílvia Ligório Fialho; Armando Silva-Cunha (MDPI AG, 2023)
Mometasone furoate (MF) is a medium-potency synthetic glucocorticosteroid with anti-inflammatory, antipruritic, and vasoconstrictive properties. However, its role in the treatment of ocular inflammation has not yet been explored. This work investigated the anti-inflammatory activity of MF in ocular tissues. First, the in vivo safety of the intravitreal (IVT) injection of MF (80, 160, and 240 µg) was evaluated via clinical examination (including the assessment of intraocular pressure), electroretinography (ERG), and histopathology. Second, MF was tested in an experimental model of bacillus Calmette-Guérin (BCG)-induced uveitis in Wistar rats. Intraocular inflammation was then evaluated via a slit-lamp and fundus examination, ERG, histopathology, and the quantification of pro-inflammatory markers. Intravitreal MF showed no toxicity in all the investigated doses, with 160 µg leading to attenuated disease progression and improvement in clinical, morphological, and functional parameters. There was a significant reduction in the levels of inflammatory markers (myeloperoxidase, interleukins 6 and 1β, CXCL-1, and tumor necrosis factor-alpha) when compared to the levels in untreated animals. Therefore, MF should be further investigated as a promising drug for the treatment of ocular inflammation.